PERAN GURU DALAM PENINGKATAN KEDISIPLINAN SISWA : Analisis Penerapan Salat Duha Berjama’ah di MTs Midanutta’lim Jogoroto Jombang - Khumairoh An Nahdliyah; Noor Fatikah; Sri Hardianti (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
A teacher has a very important role in developing the character and attitude of the Duha prayer discipline towards students in school. Discipline is a strict rule in which the contents and formulation of the rules are carefully thought out and developed in a more real way so that what is desired can be realized as expected. Discipline can give birth to the spirit of appreciating time, not wasting it. This research is a qualitative field research, the form of research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that: the role of fiqh teachers in improving student discipline through prayer in congregation at MTs Midanutta'lim Mayangan Jogoroto Jombang includes habituation, enforcing discipline, awareness, supervision, and examples or role models. Supporting factors for fiqh teachers in an effort to improve discipline in congregational prayer among students are facilities, natural resources, and support from the surrounding community. Barriers to fiqh teachers in an effort to improve discipline in congregational prayer among students. namely the lack of awareness of students and their different family backgrounds. Meanwhile, the solution for fiqh teachers in overcoming obstacles in an effort to improve discipline in congregational prayer is: providing guidance to students and the participation of parents at home.